The Influence of Accountability, Transparency and Promotion on Loyalty - Moch Muqowwil Hujjaj (Universitas Negeri Semarang, 2023)
This research was conducted at the NU MWC NU Amil Zakat, Infaq and Sedekah Institutions, Kaliori District. The purpose of this study is to prove the effect of accountability, transparency and promotion on the loyalty of donating at the Amil Zakat, Infaq and Sedekah Institutions NU MWC Kaliori District. The sampling method in this study used stratified sampling. The data collection technique in this study used a survey method by distributing questionnaires to 99 respondents consisting of administrators and members of LazisNU Kaliori District. The data analysis technique in this study used multiple linear regression analysis. The results of this study indicate that: 1) Accountability has a positive and significant effect on the loyalty of administrators and members of LazisNU Kaliori District. 2) Transparency has a significant positive effect on the loyalty of management and members of LazisNU Kaliori District. 3) Promotion has a significant positive effect on the loyalty of management and members of LazisNU Kaliori District. Accountability, transparency and promotion can explain the loyalty variable by 54.2%, while the remaining 46.8% is explained by other factors outside the research model